An investigation of carboxylated chitosan hydrogel electrolytes for symmetric carbon-based supercapacitors at low temperatures - Lin, Chen-Hsueh; Li, Wei-Cheng; Cheng, Tsung-Tien; Wang, Po-Hsin; Lee, Wei-Ni; Wen, Ten-Chin (Journal of the Taiwan Institute of Chemical Engineers, 2021)
•Bound water proportion increase with increase in the degree of carboxylation (DC).•Activation energy decrease with increase in the DC.•CCS6 with highest DC remains 57.2% of specific capacitance at -7 °C. Chitosan (CS) is the most abundant cationic biopolymer on earth. However, the ionic conductivity performance of CS polymer electrolyte is relatively poor, restricting the application in energy storage devices. Subject to carboxylation at pH of 6. 8, and 10, CS turns into CCS6, CCS8, and CCS10 respectively with the DC of 100.9%, 20.0%, and 17.8%, respectively. From the Arrhenius plot, the activation energy of CS, CCS6, CCS8, and CCS10 electrolytes is estimated as 11.7, 2.5, 2.6, and 2.6 kJ/mol respectively. As for supercapacitor performance, CCS6 remains 57.2% capacitance but the others remain 0% with decreasing temperature from 25 °C to -7 °C. At -7 °C,  only CCS6 supercapacitor shows relaxation peak in loss tangent versus frequency plot around 2  × 105 Hz according to dissociated ion pairs, being attributable to the existence of bound water. Three water states are examined by Differential Scanning Calorimetry (DSC) and Raman, verifying that CCS6 possesses high bound water proportion of 24.7%. With the highest DC, CCS6 possesses the almost equivalent amine and carboxyl groups in one glucosamine unit to play an important role to enhance dissociation, defer the breakpoints of ionic conductivity, and remain certain proportion of bound water for promising capacity at low temperature. [Display omitted]